1D-3D Simulation of Swirl Flow in Toyota K3-VE SI Engine using Ricardo WAVE and ANSYS Fluent - Akmal Fakhri, Fadhil
To reduce global fuel consumption, engineers have been trying to design the most efficient engine. One way to increase the efficiency of a combustion engine is by inducing swirl flow in its cylinder that causes an increase in turbulence resulting in a shorter combustion duration and more power. Swirl flow in the engine cylinder can be formed by using guide vanes swirl and tumble device (GVSTD) in the intake port. Swirl flow can also increase losses, so it is necessary to analyze the impact of swirl flow on engine performance. For this reason, simulations are conducted using ANSYS Fluent for CFD simulation of intake ports and Ricardo WAVE for 1D simulation of engine operation. Toyota Avanza that uses Toyota K3VE